Decadal‐Scale Recovery of Carbon Stocks After Wildfires Throughout the Boreal Forests. Issue 8 (21st August 2020) - Palviainen, M.; Laurén, A.; Pumpanen, J.; Bergeron, Y.; Bond‐Lamberty, B.; Larjavaara, M.; Kashian, D. M.; Köster, K.; Prokushkin, A.; Chen, H. Y. H.; Seedre, M.; Wardle, D. A.; et al.
Abstract: Boreal forests store 30% of the world's terrestrial carbon (C). Consequently, climate change mediated alterations in the boreal forest fire regime can have a significant impact on the global C budget. Here we synthesize the effects of forest fires on the stocks and recovery rates of C in boreal forests using 368 plots from 16 long‐term (≥100 year) fire chronosequences distributed throughout the boreal zone. Forest fires led to a decrease in total C stocks (excluding mineral soil) by an average of 60% (range from <10% to >80%), which was primarily a result of C stock declines in the living trees and soil organic layer. Total C stocks increased with time since fire largely following a sigmoidal shape Gompertz function, with an average asymptote of 8.1 kg C m −2 . Total C stocks accumulated at a rate of 2–60 g m −2  yr −1 during the first 100 years. Potential evapotranspiration (PET) was identified as a significant driver of C stocks and their post‐fire recovery, likely because it integrates temperature, radiation, and the length of the growing season. If the fire return interval shortens to ≤100 years in the future, our findings indicate that many boreal forests will be prevented from reaching their full C storage potential. However, our results also suggest that climate warming‐induced increases in PET may speed up the post‐fire recovery of C stocks. Key Points: Potential evapotranspiration was a significant driver of carbon stocks and their post‐fire recovery Carbon stocks accumulated at a rate of 2–60 g m −2  yr −1 during the first 100 years after forest fire If the fire return interval shortens to ≤100 years, many boreal forests will be prevented from reaching their full carbon storage potential